Proximal Junctional Kyphosis Following Adolescent Idiopathic Scoliosis Correction. Issue 1 (17th March 2021) - Ha, Alex S.; Park, Paul J.; Levitsky, Matthew M.; Konigsberg, Matthew W.; Kim, Yongjung J.
Abstract : Proximal junctional kyphosis (PJK) following surgical correction of adolescent idiopathic scoliosis (AIS) is a postoperative radiographic finding observed in the sagittal plane. Development of PJK has not been shown to lead to a negative clinical outcome following spinal fusion for AIS. Long-term satisfactory outcome following spinal deformity surgery is related to the status of the sagittal plane. Proper understanding and prevention of PJK in AIS surgery is needed to preserve the best sagittal plane following surgical correction of AIS.